2007
DOI: 10.1038/sj.bjc.6603709
|View full text |Cite
|
Sign up to set email alerts
|

Non-standard management of breast cancer increases with age in the UK: a population based cohort of women ⩾65 years

Abstract: Evidence suggests that compared to younger women, older women are less likely to receive standard management for breast cancer. Whether this disparity persists once differences in tumour characteristics have been adjusted for has not been investigated in the UK. A retrospective cohort study involving case note review was undertaken, based on the North Western Cancer Registry database of women aged X65 years, resident in Greater Manchester with invasive breast cancer registered over a 1-year period (n ¼ 480). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 26 publications
8
76
0
2
Order By: Relevance
“…These results confirm that the degree of comorbidity is a significant factor for HCPs in determining treatment options for older patients with operable breast cancer thus arguably reflecting why comorbidities are often stated as a reason for treating patients with PET [21,24] Age also appears to be an independent factor that HCPs consider to be important when making a treatment decision in this population. This being consistent with several studies that have identified a reduction in surgery rates with increasing age for older patients with operable breast cancer [4,25,26]. This is most likely due to chronological age often being used by HCPs as a surrogate marker for other factors that are more difficult to quantify, such as life expectancy and frailty [27].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…These results confirm that the degree of comorbidity is a significant factor for HCPs in determining treatment options for older patients with operable breast cancer thus arguably reflecting why comorbidities are often stated as a reason for treating patients with PET [21,24] Age also appears to be an independent factor that HCPs consider to be important when making a treatment decision in this population. This being consistent with several studies that have identified a reduction in surgery rates with increasing age for older patients with operable breast cancer [4,25,26]. This is most likely due to chronological age often being used by HCPs as a surrogate marker for other factors that are more difficult to quantify, such as life expectancy and frailty [27].…”
Section: Resultssupporting
confidence: 72%
“…Older patients have higher rates of comorbidity and frailty so that the risk of death from breast cancer is relatively reduced, with only 23% deaths due to breast cancer for patients diagnosed in their mid-80s compared to 73% for patients diagnosed in their 50s [3]. Older patients with operable breast cancer may be offered alternative treatment modalities, such as primary endocrine therapy (PET) [4,5], wherein oestrogen receptor (ER) positive disease may be treated with endocrine therapy alone.…”
Section: Introductionmentioning
confidence: 99%
“…In the stabilization process must be weight in is the under treatment of older breast cancer patients. Studies have found that increased patient age is associated with decreased guideline concordandce for definitive surgery, adyuvant chemotherapy and adjuvant hormonal therapy, after adjusting for risk factor and tumor characteristics [5,16,12]. Under treatment has shown to increase mortality for breast cancer [5].…”
Section: Discussionmentioning
confidence: 99%
“…Differential treatment for breast cancer by age has been observed. 47 Prevalent comorbidity is likely to play an important part in accelerating death in the first year after diagnosis because of the contraindication of effective treatment or more severe complications of treatment amongst patients with comorbid conditions. This is one of the explanations that has been given for the fact that older women receive less surgery compared with younger women in West Midlands.…”
Section: Possible Causal Explanationsmentioning
confidence: 99%